Filipinas Journal of the Philippine Studies Association, Inc. - Testa-de Ocampo, Anna Melinda (Philippine Studies Association, Inc. and through a grant from the National Commission for Culture and the Arts, 2021)
The articles printed in this fourth volume of Filipinas (2021) include plenary speeches and selected papers presented in the recent Philippine Studies Association Conference, "500 years of christianity in the Philippines," on 25-27 August 2021 online. The year 2021 is a significant year as it marks the 500th anniversary of the arrival of the Portuguese Ferdinand Magellan and his Italian chronicler, Antonio Pigafetta in Cebu in 1521. In the same manner of the reassessment of the 500 years after the arrival of Christopher Columbus in the Americas in 1492, here in the Philippines -a re-evaluation of Philippine historiography, history, archaelogy, etc., of the Spanish colonial period has been undertaken by several scholars here and abroad. A re-examination of the historical research and readings of this event, and the effects of colonization over the years are crucial especially at this juncture.